OSL and TL retrospective dosimetry with leucite glass-based dental ceramics. (September 2017) - Ekendahl, Daniela; Judas, Libor
Abstract: Dental ceramics are radiation sensitive materials and exhibit luminescent properties. Their samples can be potentially used for individual dose assessment in situations where retrospective dosimetry is required. In this work, we investigated dosimetry properties of two leucite glass-based dental ceramics using Optically Stimulated Luminescence (OSL) and Thermoluminescence (TL). We concentrated on characteristics as reproducibility, fading, optical bleaching, minimum detectable dose (MDD), dose response and photon energy response of TL and OSL signals. Both the dental ceramics exhibited very good reproducibility (<5% at 2σ level) when irradiated and measured repeatedly. Their luminescence response was found to be linear for a wide range of doses up to 8.5 Gy. The MDD values for the samples investigated were a few mGy. The ceramics are not tissue equivalent materials, and their luminescent signals measured were strongly dependent on incident photon energy. Because of fading and optical bleaching the OSL and TL signals were not stable in time. Especially optical bleaching represents a main limiting factor for dose reconstruction. However, one of the ceramics provided a relatively resistant high temperature TL peak for dosimetry. Highlights: Leucite glass-based dental ceramics were considered for retrospective dosimetry. Their dosimetry application was based on use of OSL and TL. TL and OSL signals exhibit linear dose response. Dose reconstruction can be impaired by fading, non-ideal photon energy response and especially by optical bleaching.